Simple and Low-Cost Rapid Prototyping fabrication by Using a Photolithography (Journal of University of Babylon for Engineering Sciences, 2023)
This work describes improvements to the original process, including reduced cost of fabrication. It has successfully overcome all of the major hurdles the semiconductor industry roadmap provides. To accomplish that, it has experienced significant modifications and has substantially broadened the frontiers of optical and electronics research and engineering. Photolithography is the essential stage in the semiconductor fabrication process that determines chip quality. Because the fabrication process is a batch process with varying chip quality, uniformity has always been a primary goal of the process. This case study focuses on improving the photolithography step in order to improve uniformity and critical dimension accomplishment, both of which are quality parameters for semiconductor devices. should be examined for improved optimization. This paper will discuss the most current improvements in the Photolithographic process, as well as the incorporation of a variety of resolution-enhancing approaches. A photoresist layer (Photosensitive Dry Film 1 meter for Circuit Photoresist Sheet 30 cm Width) is applied to the material to be patterned. The photoresist layer is exposed to ultraviolet (UV) radiation through the mask. This stage is completed in a mask aligner, which aligns the mask and wafer prior to the subsequent exposure stage. Depending on the mask aligner generation, the mask and substrate are brought into contact or close proximity (contact and proximity printing). Depending on whether positive or negative photoresist was used, the exposed or unexposed photoresist components were removed during the resist development process. Mask design is created, it can produce various mask designs in micro level scale (um) as a DWG file by AutoCAD program. DWG file is converted to a PDF file with a PDF converter. The resulting PDF file mask design is printed as positive film. in this experiment, uniform layer glass is used as substrate, aluminum deposited with a length of 2.5 cm and width of 2.5 cm with thickness 0.2 cm.